Discovery of a Byzantine Church in Iznik/Nicaea, Turkey: an Educational Case History of Geophysical Prospecting with Combined Methods in Urban Areas. Issue 1 (24th September 2014) - Rabbel, W.; Erkul, E.; Stümpel, H.; Wunderlich, T.; Pašteka, R.; Papco, J.; Niewöhner, P.; Bariş, Ş.; Çakin, O.; Pekşen, E.
Abstract The city of Iznik, called Nikaia or Nicaea in ancient times, is located in northwest Anatolia, Turkey. Nicaea is renowned especially for the first Council of Nicaea convened by the Roman emperor Constantine in ad 325 in an attempt to unify the Church. During an international field course on the geophysical exploration of archaeological targets we detected the remains of a small previously unknown Byzantine church on a fallow lot of land inside the city. The church is oriented parallel to the ancient Hippodamian street grid that deviates from the modern street system of the quarter by ~45°. We found the contours of the nave, two aisles and three apses as well as evidence of a partly refilled grave. The geophysical measurements indicate that the foundations of the church consist of low‐porosity hard rock with a low magnetic susceptibility, probably limestone or sandstone embedded in fluvial sediments. The field study is based on ground‐penetrating radar (GPR), magnetics, electric resistivity tomography (ERT) and microgravimetry. It highlights the strength and necessity of combining different geophysical methods in exploring and characterizing archaeological sites. In fact, the foundation walls of the church do not show any magnetic anomaly but could be delineated clearly only by GPR. The wall remains appear as highly resistive spots in ERT. By converting the three‐dimensional GPR image into an electric resistivity model we could verify that the ERT results fully correspond to the ruins found by GPR. The structure interpreted as a loosely refilled grave is indicated mainly by a weak gravity anomaly (~9 μGal) and a diffuse reflection pattern in GPR. Electric forward modelling shows that this structure leads to an additional increase of a high resistivity anomaly, which is primarily caused by foundation rocks, but it cannot be resolved within the ERT pattern a priori. Copyright © 2014 John Wiley & Sons, Ltd.